The Power of Structure in Exchange - Pfeiffer, Matthew (TRAILS: Teaching Resources and Innovations Library for Sociology, 2015)
The objective of this exercise is to emphasize the importance of environmental factors in exchange – specifically, an actor’s position within a network. Research on network exchange theory (NET) has a long history of examining how the structure of a network influences exchange, noting how network structure can both encourage and discourage exchanges. This exercise, developed for upper-level students studying social psychology/NET, also aims to clarify the assumptions of NET, the differences between strong and weak networks, and the way in which network structures are likely to break. The latter is calculated using the graph-theoretic power index (GPI): a formula based upon the counting of path lengths. This assignment is best used in a smaller class, although it can be adapted for larger classes.